Democracy, politics and participation: the museologist Waldisa Rússio (Cadernos de Sociomuseologia, 2018)
In this issue, they are showed and analyzed professional and personal aspects of Waldisa Rússio Carmago Guarnieri path. It is presented her family references in her activities, specially, the influence of her grandfather and mother. Her social origin, gender and schooling are highlighted in order to observe her professional performance. The aim is pointing out that her ideas about workers and work conditions became important structures since they developed her worldview and her way to handle work routine. This context provides why she struggled for the social work dimension in the musuologist career. If it is considerate her path in São Paulo public service, besides her master and doctorate degrees, Waldisa has a singular position in Brazilian museology field. Moreover, this paper presents a political perspective about her career and that it is not usually mentioned. In the political-administrative dimension, it is emphasized her participation in the elaboration of culture and museological policies. To sum up, it is possible to see that Brazilian woman assumed a critical position in the field which she worked because it was a strategy took by her to be heard and authorized in museology. Therefore, it is admited that Waldisa’s political behavior was related to the context that she lived. Finally, it is noticed that some challenges who were perceived in the eighties remain nowadays in those fields.Keywords: Waldisa Rússio Camargo Guarnieri; museological policy, participation,